230k views
0 votes
I need help asap someone please help me i dont understand this question so can someone help me

I need help asap someone please help me i dont understand this question so can someone-example-1
User Jvdbogae
by
6.0k points

1 Answer

4 votes

Answer:

we conclude that:


(2p)/(4p^2-1)/ (6p^3)/(6p+3)=(1)/(2p^3-p^2)

Explanation:

Given the expression


(2p)/(4p^2-1)/ (6p^3)/(6p+3)


\mathrm{Apply\:the\:fraction\:rule}:\quad (a)/(b)/ (c)/(d)=(a)/(b)* (d)/(c)


=(2p)/(4p^2-1)* (6p+3)/(6p^3)


=(2p)/(4p^2-1)* (2p+1)/(2p^3)


\mathrm{Multiply\:fractions}:\quad (a)/(b)* (c)/(d)=(a\:* \:c)/(b\:* \:d)


=(2p\left(2p+1\right))/(\left(4p^2-1\right)* \:2p^3)

cancel the common factor: 2


=(p\left(2p+1\right))/(\left(4p^2-1\right)p^3)

cancel the common factor: p


=(2p+1)/(p^2\left(4p^2-1\right))


=(2p+1)/(p^2\left(2p+1\right)\left(2p-1\right))

cancel the common factor: 2p+1


=(1)/(p^2\left(2p-1\right))

Expanding


=(1)/(2p^3-p^2)

Thus, we conclude that:


(2p)/(4p^2-1)/ (6p^3)/(6p+3)=(1)/(2p^3-p^2)

User Lvogel
by
6.1k points